PENGARUH MODEL PEMBELAJARAN RECIPROCAL TEACHING TERHADAP HASIL BELAJAR MATEMATIKA DITINJAU DARI KEMANDIRIAN BELAJAR PESERTA DIDIK - Laila Hidayah; Satrio Wicaksono Sudarman; Ira Vahlia (UNIVERSITAS MUHAMMADIYAH METRO, 2019)
The study aims to find out 1) whether or not there is an effect of the Reciprocal Teaching model on students' mathematics learning outcomes. 2) which ones have good mathematical learning outcomes between those who have high, moderate learning independence. 3) interactions between Reciprocal Teaching and conventional learning models. The data analysis technique uses hypothesis testing of two-way anava with unequal cells. Research conclusions: 1) There is an influence of mathematics learning outcomes between those who learn using the Reciprocal Teaching and conventional learning models. 2) Mathematics learning outcomes that have high learning independence are better than those with moderate learning independence and mathematics learning outcomes that have moderate independence are better than those with low learning independence. 3) There is an interaction between Reciprocal Teaching and conventional learning models and learning independence on mathematics learning outcomes in those who have high, medium and low learning independence.